An Optical Set-Up For Inspecting Edge Chipping Defects Of Dws Solar Wafer - Lim, Thai Li (2019)
Diamond-Wire Sawn (DWS) technique in Photovoltaic (PV) wafer slicing has the capability to slice out thinner wafers at a faster speed and lower kerf lost. However, thinner wafers will cause higher breakage rate. In-line inspection of defects such as wafer’s edge chipping has become more important. This research focuses on the optical set-up for silicon solar wafer’s edge chipping inspection system, resulting in the proposal of a novel set-up. It was discovered that the optimum camera set-up is at 45° and this angular view achieved surface visibility above 70% for all the three surfaces of a wafer’s edge, i.e., the top, side, and bottom surfaces. The use of dome light in the set-up was proven effective in generating best image quality for DWS surface with SNR of 14.4dB. Also, the back-lit illumination resulted in the best contrast averaging at 85.0%. The proposed set-up is applicable to run in-line on 353.7 mm/s of conveyor speed, which is equivalent to 4200 UPH production with the wafers pitch of 300 mm per unit. It achieved 100% detection for the three major types of chippings which are (i) the non-through, (ii) the through, and (iii) the side chipping, for chipping samples with size between 33 μm to 780 μm. The correctness of defect region segmentation scores 68.1% with false negative about 31.9% while the false positive maintained at 2.3%.